Familial occurrence of warts, hypogammaglobulinemia, infections, and myelokathexis (WHIM) syndrome - Siedlar, Maciej (Birkhäuser-Verlag, 2008)
INTRODUCTION: Warts, hypogammaglobulinemia, infections, and myelokathexis (WHIM) syndrome is a rare immunodeficiency disorder with an autosomal-dominant pattern of inheritance and low fatality rate but significant lifelong morbidity. MATERIALS AND METHODS: A 27-year-old mother of two children has been suffering from severe neutropenia and recurrent infections with the diagnosis of sporadic WHIM syndrome established by sequencing the CXCR4 gene and the finding of a heterozygous 1000 C→T nonsense mutation in the second CXCR4 exon. The first child was an apparently healthy boy delivered at full term. Umbilical cord blood cells were obtained for genetic analysis. Peripheral blood cells were also analyzed at 8 months of life. Both analyses revealed the same mutation as that of his mother. The child was in a good condition, manifesting neutropenia without infections until 11 months of life. He subsequently developed pneumonia requiring a more aggressive treatment. After that, the regular substitution of immunoglobulins (IVIGs) and G-CSF has been preventing serious infections. Six months ago the second boy was delivered who also demonstrated neutropenia without severe infections. Genetic studies using cord blood and also peripheral blood cells in the fourth month showed an identical mutation of the CXCR4 gene as in his mother. Moreover, the mother and her first son demonstrated monocytopenia. RESULTS: The results indicate that genetic defects connected with WHIM syndrome may influence not only the granulocyte, but also the monocytic lineage. Moreover, a perinatal diagnosis of WHIM syndrome made by sequencing the CXCR4 gene should be performed in cases where either parent is known to be affected with this disease. CONCLUSIONS: This would facilitate an earlier detection of the deficiency in children, thereby allowing a more comprehensive follow-up and administration of appropriate therapy.